2013
DOI: 10.1093/aje/kwt112
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain Amino Acid Intake and the Risk of Diabetes in a Japanese Community: The Takayama Study

Abstract: Dietary supplementation with branched-chain amino acids (BCAAs), including leucine, isoleucine, and valine, has shown potential benefits for the metabolic profile. However, higher blood BCAA levels have been associated with insulin resistance. To our knowledge, there has been no study on dietary BCAAs and the risk of diabetes. We examined the association between BCAA intake and risk of diabetes in a population-based cohort study in Japan. A total of 13,525 residents of Takayama City, Japan, who enrolled in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 32 publications
4
87
6
Order By: Relevance
“…BCAAs also were increased in parallel with more severe metabolic syndrome factors, including waist-hip ratio and ALT. These findings are nearly identical to previously reported results [1][2][3][5][6][7]10].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…BCAAs also were increased in parallel with more severe metabolic syndrome factors, including waist-hip ratio and ALT. These findings are nearly identical to previously reported results [1][2][3][5][6][7]10].…”
Section: Discussionsupporting
confidence: 93%
“…In a large-scale epidemiologic study, persons with elevated serum BCAAs later had a high rate of type 2 DM onset [6]. On the other hand, high intake of BCAAs has also been reported to reduce type 2 diabetes onsets [7]. Therefore, we measured serum BCAA levels in type 2 DM, NAFL, and/or obese patients and examined the correlation with clinical parameters.…”
Section: Introductionmentioning
confidence: 98%
“…Regarding the BCAA intake, our results were similar to the US adult population, in that the major food contributors were red meat (~37%), milk (~12%) and fish (~8%) [6]. However, these results are different from those observed in Japan, whose lowest food contributor with total BCAA intake in the adult population was red meat with approximately 14.9% of consumption in men and 13.7% in women [5]. …”
Section: Discussionsupporting
confidence: 69%
“…Several studies have shown that elevated levels of BCAA in blood, including Leu, Ile and Val, may be related to the risk of developing type 2 diabetes, insulin resistance and cardiovascular diseases [4,5,6,7]. These noncommunicable diseases (NCD) are the major causes of death worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Although evidence has supported the association of higher BCAAs with T2D, the causality of this association remains unclear. As essential amino acids, dietary or supplemental BCAAs seem to have beneficial effects on body weight, lean body mass, and diabetes prevention (Nagata et al 2013; Qin et al 2011). It has been proposed that elevated BCAA metabolites due to reduced BCAA catabolism or increased tissue protein breakdown, not BCAAs per se, cause insulin resistance and diabetes (Lynch and Adams 2014; Mayers et al 2014; Tai et al 2010).…”
Section: Discussionmentioning
confidence: 99%